Developing a problem-based learning module on organs of movement of animals and human theme, humans and the environment sub-theme, for thematic learning to improve fifth-grade students' critical thinking (Lighthouse Publishing, 2023)
The aim of this study was to develop a valid problem-based thematic learning module on the theme of organs of movement of animal and human, sub-theme of humans and the environment, practical and effective in improving students' critical thinking. The type of research and development used refers to the R&D theory of Borg and Gall. The population of this research was Sriwijaya 1 Public Elementary School, Bandar Mataram District, Central Lampung Regency with a target of 2 educators. The sample of this study was 31 students in class VA and 32 students in VB at Sriwijaya 1 Public Elementary School Sub-district who were selected through purposive sampling technique. Data collection techniques in the form of observation, questionnaires, and tests. Data analysis used quantitative descriptive and quantitative analysis. Then quantitative analysis with t test and proportion test to test the effectiveness. The results of this study indicated that thematic teaching materials based on problem-based learning models developed using Borg and Gall's R&D steps of thematic learning for fifth graders of Elementary School. Theme 1 with sub-theme 2 were feasible and effective in improving students' critical thinking.